3D printing and 3D-printed electronics: applications and future trends in smart drug delivery devices - Ma, Wai Cheung (2023)
Drug delivery devices which can control the release of drugs on demand allow for improved treatment to a patient. These smart drug delivery devices allow for the release of drugs to be turned on and off as needed, thereby increasing the control over the drug concentration within the patient. The addition of electronics to the smart drug delivery devices increases the functionality and applications of these devices. Through the use of 3D printing and 3D-printed electronics, the customizability and functions of such devices can also be greatly increased. With the development in such technologies, the applications of the devices will be improved. In this review paper, the application of 3D-printed electronics and 3D printing in smart drug delivery devices with electronics as well as the future trends of such applications are covered.